Plut, šut e durak: algumas notas feitas à leitura de M. Bakhtin - Velmezova, Ekaterina (Organon, 2009)
The aim of this study is to analyse the social roles of three characters – the swindle, thenaive and the buffoon, in Mikhail Bakhtins’ research entitled Formy vremeni i xronotopa v romane.Očerki pó istoričeskoj poètike [ Forms of time and chronotopos in novel]. We intend to investigate howthese characters can represent different maks and at the same time different ways of answering to rulesand to social psychology of russian-soviet people.